SOSIALISASI INVESTASI SAHAM SYARIAH UNTUK MENINGKATKAN LITERASI KEUANGAN MASYARAKAT DUSUN KEMPUL - Arifah Arifah; Saryadi Saryadi; Miqdam Maufur (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
The low financial literacy of rural communities, particularly concerning Sharia stock investment, poses a challenge in realizing Islamic values-based economic self-reliance. This community service activity was conducted in Kempul Hamlet as a response to the minimal public understanding of Sharia-compliant investment concepts and mechanisms. The primary goal was to increase the understanding and awareness of residents—who are predominantly Muslim and interested in the Sharia economy—regarding Sharia financial literacy, and to encourage their participation in the Sharia capital market. The method used was Participatory Action Research (PAR), consisting of five stages: diagnosing, action planning, action taking, evaluating, and specifying learning. Implementation involved face-to-face socialization, interactive discussions, Sharia stock account opening simulations, and introduction to digital investment applications. The results showed that participants achieved a significant increase in understanding on average and expressed interest in trying Sharia stock investment. The formation of independent study groups post-activity also serves as a positive indicator of sustainability. The synergy between the service team, village leaders, and resource persons from the Indonesia Stock Exchange (IDX) and securities firms was key to the program's success, ultimately encouraging the growth of an inclusive and sustainable financial ecosystem at the village level.